The Representation of Moral Values in Mahmoud Darwish's Poem Fii Bayti Ummī Sūratī Tarnū Ilayya: A Semiotic Study by Michael Riffaterre - Indah Natisha Maura; Rohanda; Ridho Hidayat (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study aims to analyse the representation of moral values in Mahmoud Darwish's poem Fii Bayti Ummī Sūratī Tarnū Ilayya. This study uses a qualitative approach with a descriptive-analytical method. The formal object of this study is Michael Riffaterre's semiotic theory, while the material object is the poem itself. The analysis was conducted through heuristic and hermeneutic reading and hypogram tracing to reveal the literal, symbolic, and intertextual meanings in the poem. The results show that this poem represents an inner dialogue between the poet and his past self as a reflection on identity and change. Symbols such as self-image, walls, and heavenly gardens contain moral values in the form of honesty towards oneself, existential awareness, and moral responsibility in facing the dynamics of life. This study concludes that Mahmoud Darwish's poetry not only displays the beauty of language but also contains relevant moral messages, especially regarding the importance of self-reflection and the search for truth in the midst of changing times. Keywords: Moral, Poem, Michael Riffaterre's